Rhythm in Architecture: an Aesthetic Appeal - Thapa, Rena (Journal of the Institute of Engineering, 2018)
It is a discourse that exhibits the presence of rhythm in visual art, especially the architecture that holds strong aesthetic appeal. In this paper, the introduction part focuses on how rhythm generally reinforces aesthetic experiences in human sensory. Rhythm in architecture means recurrence of elements such as lines, shapes, forms or colors resulting on organized movement in space and time. I have taken the best analogy and examples of rhythm present in nature which has been formulated by scientist as Fibonacci number. I have tried to show architectures incorporating rhythm in different epoch of human civilization around the globe that have been popular and remarkable till the date. These architectural monuments have become aesthetic timeless entity, such as pyramids in Egypt, Parthenon in Greece, gothic architecture of medieval Europe, Tajmahal in India, Hindu temples and Buddha stupas in Nepal etc. Similarly modern architecture has been in equal focus in this article despite its unique and functional structures. The paper has been concluded with the strong statement that however the sense of beauty is shaped by cultural experience, rhythm is frequently desired with architectural compositions. These qualities are often universally admired and celebrated irrespective of time and place. Journal of the Institute of Engineering, 2017, 13(1): 206-214